Burnout Ditinjau dari Kesejahteraan Psikologis pada Pegawai di Pengadilan Negeri Medan - Aritonang, Elsea Rachellea; Hartini, Sri; Br Parapat, Deby Cristy; Pradiva, Angie Anggelin; Elvinawanty, Rianda; Aritonang, Marsela Giovani (Dinasti Research, 2026)
This research aimed to ascertain the correlation between psychological well-being and burnout among personnel at the Medan District Court. This research is grounded on the significant work demands that may diminish psychological well-being and elevate the risk of burnout. The research used a quantitative methodology. A total of 142 workers were chosen as study participants via a purposive sample method. Data were gathered using surveys. The study's findings indicated a substantial negative correlation between psychological well-being and burnout, with a correlation coefficient of r = -0.241 and a p-value of 0.004 (p < 0.05). These findings reveal a substantial inverse correlation, characterised by a strong and critical association between these factors. The coefficient of determination for the Psychological Well- being indicator was measured at 0.058, representing 5.8% of Burnout.